2012
DOI: 10.7314/apjcp.2012.13.10.5251
|View full text |Cite
|
Sign up to set email alerts
|

Is the MDR1 C3435T Polymorphism Responsible for Oral Mucositis in Children with Acute Lymphoblastic Leukemia?

Abstract: Background and Aim: Although the functional consequences of MDR-1 polymorphisms have been the subject of numerous studies, to the best to our knowledge, associations with clinical side effects of anticancer drugs have yet to be assessed. Our aim was to clarify any role of the C3435T polymorphism of the MDR1 gene in oral mucositis and its relation with elevated reactive oxygen species (ROS) levels, in children with acute lymphoblastic leukemia (ALL). Materials and Methods: The distribution of the MDR-1 C3435T p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…All the cases had a confirmed diagnosis of leukemia and the controls were mainly matched for age and sex. Among the included studies, six studies were conducted in an Asian population, 25 , 28 , 31 , 34 , 36 , 38 nine studies in a Caucasian population, 22 – 24 , 26 , 29 , 30 , 32 , 33 , 35 and two studies in a mixed population. 27 , 37 The distribution of genotypes among the control groups in four studies was not in agreement with HWE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the cases had a confirmed diagnosis of leukemia and the controls were mainly matched for age and sex. Among the included studies, six studies were conducted in an Asian population, 25 , 28 , 31 , 34 , 36 , 38 nine studies in a Caucasian population, 22 – 24 , 26 , 29 , 30 , 32 , 33 , 35 and two studies in a mixed population. 27 , 37 The distribution of genotypes among the control groups in four studies was not in agreement with HWE.…”
Section: Resultsmentioning
confidence: 99%
“… 27 , 37 The distribution of genotypes among the control groups in four studies was not in agreement with HWE. 22 , 33 , 35 , 36 …”
Section: Resultsmentioning
confidence: 99%
“…According to our result, we also suggested that the CT genotype might be a susceptibility factor for infertility. Bektaş-Kayhan et al (2012) also described that children with acute lymphoblastic leukemia carrying the CT genotype are more prone to develop oral mucositis and might therefore also be more susceptible to the side effects of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that functional polymorphisms in gene MDR1 might influence the course of the disease, as it has been reported that children carrying the CT (C3435T) genotype are more prone to develop oral mucosistis (Bektas-Kayhan et al, 2012).…”
Section: Madara Kreile Et Almentioning
confidence: 99%